(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2011)
Intellectual capital is the subject of discussion in academic and business space, deciding on how to capitalize on this is a matter of today, coupled with this are the International Accounting Standards as a standard option of applying accounting policies and principles to the organization search for competitiveness, as well as IAS 38 identifies the intangible assets associated with favorable as a tool for the assessment of intellectual capital. Based on the above described this article aims to provide a methodological approach that allows the assessment and registration of intellectual capital as an intangible asset in the financial statements of organizations based mainly on the International Accounting Standard No. 38, to serve this purpose is theoretical support research publications IASB regarding intangible assets and intellectual capital refers to is based on the theories of writers such as Brooking (1997), Edvinsson (1998), Edvinsson (2003). The methodology used was an empirical, descriptive, non-experimental design. The study population was addressed through a survey of CPAs members of the Disclosure Committee International Accounting Standards of the Association of Chartered Accountants of Zulia state, data collection was conducted through a standard instrument questionnaire, validated by three experts, two of the area and an area accounting methodology. Data were analyzed with simple statistics. In conclusion it was found that there is a deficiency in knowledge and management methodologies for the valuation and accounting of Intellectual Capital, at the end is a proposal that allows the articulation of the value of intellectual capital and its incorporation in the financial statements as a Intangible assets according to the weight given to each organization.